2013
DOI: 10.1002/jemt.22243
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic analysis of recycled paper effect on print quality parameters

Abstract: To determine whether the geometrical accuracy of small printed elements does not worsen on recycled paper, microscopic analysis of the dot area and the graphic elements raggedness printed on different types of recycled and coated papers at different screen ruling was carried out. Experimental tests have shown that geometrical accuracy of small elements printed on recycled paper/cardboard, in comparison to pictures printed on primary production paper is almost the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The method of investigations of tension experiments of the paper and the devices used in the investigations were already described in reference [11]. Set of physical parameters used for one dimensional model that was applied for the analysis of tension of orthotropic materials was also determined from these experiments.…”
Section: Results Of Analysis Of Physically Non-linear Tension Of Papementioning
confidence: 99%
See 1 more Smart Citation
“…The method of investigations of tension experiments of the paper and the devices used in the investigations were already described in reference [11]. Set of physical parameters used for one dimensional model that was applied for the analysis of tension of orthotropic materials was also determined from these experiments.…”
Section: Results Of Analysis Of Physically Non-linear Tension Of Papementioning
confidence: 99%
“…9 the results of tension of paperboard in the machine direction as well as in the cross direction are presented. Here the results obtained in reference [11] are used.…”
Section: Results Of Analysis Of Experimental Investigations Of Paperbmentioning
confidence: 99%
“…Adhesion of inks to paper plays an important role in many industrial applications (Awaja et al, 2009). Kibirkštis et al (2013) showed in their research that geometrical accuracy of small elements printed on recycled paper, in comparison to pictures printed on paper produced from virgin fibres, is almost the same. Leuco dye-based thermochromic inks are today commercially available in all major ink types (such as water-based, solvent-borne and photocuring inks) for application on different substrates.…”
Section: Introductionmentioning
confidence: 99%